Noble gases, carbon and nitrogen isotopes in different lithologies of Pesyanoe: irradiation history and impact processes on the aubrite parent body - Buikin, Alexei I.; Verchovsky, A. B.; Hopp, Jens; Lorenz, C. A.; Korochantseva, E. V.; Trieloff, Mario; Ott, Uli (Geochemistry international, 2024)
We present the results of stepwise crushing and combustion analyses for noble gases, carbon and nitrogen in Pesyanoe aubrite pyroxene lithologies, composed of grey (Px-G) and light (Px-B) enstatites differing in the degree of impact processing and the number of inclusions. Our study identifies three main noble gas endmembers in Pesyanoe: a cosmogenic component, radiogenic 40Ar, and an endmember representing a mixture of solar wind and Q components in variable proportions. Based on petrographic and noble gas data we argue that these gases accumulated in the material during its regolith history and were later redistributed into gas inclusions/voids as the result of an impact event. During impact metamorphism, Px-G acquired its grey color and multiple gas inclusions were formed within it, more than in case of Px-B. Our study demonstrates for the first time: (1) The host phase of gases trapped during shock metamorphism are grains of rock-forming minerals, in particular Px-G, due to the formation of a large number of cracks in the direction of cleavage during brittle deformation, (2) The gas capture is associated not with the final stage of the formation of consolidated fragmental breccia, at which lithification of the fragments occurred, but with one of the intermediate impact events. High amounts of trapped and cosmogenic noble gases are released during the stepwise crushing—significantly higher than in case of any other studied aubrite. Some unusually high 36Ar/132Xe ratios (up to 54 780 versus 22 705 in the solar wind) were discovered during crushing of Px-G. Our preferable explanation of this phenomenon is a specific superposition of noble gas elemental fractionation processes related to the impact cratering of the Pesyanoe parent body. The carbon isotopic composition (δ13C = -21.2 ± 0.2‰, 1σ) is slightly heavier than that of the Bustee aubrite carbon. The combined use of different extraction methods made it possible to determine that the solar type and indigenous (δ15Nindig = -0.1 ± 3.2‰, 1σ) nitrogen components are located in the gas inclusions, whereas the extraneous nitrogen component (~+45‰) is chemically bound. The large cosmic ray exposure age variations (44 and 55 Ma in case of Px-G and Px-B, respectively) and the heterogeneous distribution of solar-type gases in Pesyanoe aubrite point to a diverse irradiation history of the material before breccia formation. Alternatively/additionally, cosmogenic gases (as well as solar and primordial) in Px-G may have became lost and/or partly redistributed into gas inclusions as a result of the impact event.
Gesehen am 12.05.2025